KADAR FOSFAT DALAM AIR SUNGAI CIKANIKI - Raymona Rosilla; Mia Azizah; Desy Setiawati (Universitas Nusa Bangsa, 2015)
Phosphate Content in Cikaniki RiverThe Cikaniki River is one of the tributaries of Cisadane, which crosses the provinces of West Java and Banten. This river has a very high function and value for human life and water ecosystem. Phosphates formed naturally in formed of rock and undergo a weathering process, rocks gradually break down into phosphate ions dissolved in water. Phosphates in orthophosphates are produced by nature and are found in waste, whereas polyphosphates are often used in detergents, but in water the form of poly will turn into an ortho form. The analysis to find out the phosphate content in Cikaniki River. Phosphate analysis of river water refers to SNI 06-6989.31-2005, using the uv-vis spectrophotometric method in ascorbic acid. The results showed that the phosphate content in Cikaniki River still fulfilled the Standard Quality of PP no. 82 of 2001, is <0.2 mg / L except in Kampung Babakan Liud area. Phosphate contamination in river water can be derived from natural processes as well as from the addition of contamination due to human activities in the form of agriculture, industry, and household activities and the presence of excessive phosphate can lead to explosive growth of algae in the waters.Keywords: River, Phosphate, ascorbic acid, wasteABSTRAKSungai Cikaniki adalah salah satu anak sungai Cisadane, yang melintasi Provinsi Jawa Barat dan Banten. Sungai ini memiliki fungsi dan nilai yang sangat tinggi bagi kehidupan manusia dan ekosistem air. Fosfat terjadi secara alami dalam bentuk batuan dan mengalami proses pelapukan, batuan secara bertahap mengurai menjadi ion fosfat yang larut dalam air. Fosfat dalam bentuk ortofosfat diproduksi oleh alam dan ditemukan di limbah, sedangkan polifosfat sering digunakan dalam detergen, tetapi di dalam air bentuk poli akan berubah menjadi bentuk orto. analisis untuk mengetahui kandungan fosfat di Sungai Cikaniki. Analisis fosfat pada air sungai mengacu kepada SNI 06-6989.31-2005, menggunakan metode spektrofotometri uv-vis secara asam askorbat. Hasil penelitian menunjukkan kadar Fosfat di Sungai Cikaniki masih memenuhi Baku Mutu PP No. 82 Tahun 2001, yaitu Â < 0,2 mg/L kecuali pada daerah Â Kampung Babakan Liud. Pencemaran Fosfat di air sungai dapat berasal dari proses alamiahÂ maupun berasal dari penambahan cemaran akibat aktifitas manusia yang berupa pertanian, perindustrian, maupun kegiatan rumah tangga dan keberadaan fosfat yang berlebihan dapat menyebabkan terjadinya ledakan pertumbuhan alga di perairan.Kata Kunci: Sungai, Fosfat, asam askorbat, limbah